Fabrication of ultrastable water-in-oil high internal phase emulsion as versatile delivery vehicle through synergetic stabilization. (May 2022) - Tang, Xiang-Yi; Wang, Zhi-Ming; Yu, Di; Yu, Shu-Juan; Meng, He-Cheng; Zhang, Tao; Chen, Hua-Lei; Yang, Zhan-Wei; Yang, Qing-Yu; Li, Lili
Abstract: Bioactive substances possess superior antioxidant, anti-hypertensive, and anti-tumor activities. However, their susceptibility to degrade at low pH often limit their application. Compare with the conventional oil-in-water (W/O) emulsions, the lack of natural hydrophobic stabilizers resulted in difficulties in fabricating water-in-oil (W/O) high internal phase emulsion (HIPE). Further, the instability of W/O HIPE also limit its industrial application in food industry. In the present study, a natural, conventional, eco-friendly, and structured W/O HIPE was developed using glyceryl monostearate (GMS) as emulsifier and beeswax and gellan gum as structurant. The system with the synergetic effect of emulsifier and structurant, accounted for 0.25 wt % of GMS and hydrogel, and 1.25 wt % of beeswax in total system endowed the W/O HIPE with biphasic rigid network and impressive storage stability. The microstructures of these newly developed W/O HIPEs could be controlled by the beeswax concentration ( c b ), GMS concentration ( c g ), and aqueous phase volume ( Φ ). Moreover, the GMS-based emulsion encapsulation improved the retention rate of betanin by 36.68% after 7 days of storage. Meanwhile, this emulsion gel could prevent the nucleophilic attack of hydrogen ions against betanin at room temperature under a low pH environment, which greatly improved the stability of betanin under highly acid conditions. Furthermore, the GMS stabilized W/O HIPE possessed pH-sensitive, which could achieve controlled-release of both hydrophilic and hydrophobic functional compounds in an in vitro simulated release assay. Graphical abstract: Image 1 Highlights: W/O HIPE was formed by GMS and beeswax. The stability of the W/O HIPE was significantly improved by consolidating the biphasic network. The stability of betanin was improved in the gel-in-gel HIPE. The release profile of curcumin and betanin were evaluated.